Legal Reasoning and Compensation Determination in Sharia Economics: An In-Depth Analysis of Unlawful Acts in Case 84/Pdt.G/2019/PA.Yk - Widad, Zaqil -; Saifuddin, Saifuddin (Sharia and Law Faculty of Sunan Kalijaga Islamic State University Yogyakarta, 2023)
AbstractThe limitations of regulations in determining compensation for unlawful acts prompt judges in Religious Courts to engage in legal reasoning (ijtihad). This research aims to examine the determination of compensation in Sharia Economics disputes involving unlawful acts. The case under investigation is case number 84/Pdt.G/2019/PA.Yk, the plaintiff demands compensation as the defendant closed the BTN Sharia savings account without prior confirmation. The judicial panel upheld the compensation claim, referencing Articles 1375 and 1372 of the Indonesian Civil Code (KUHPerdata) and jurisprudence number 650/PK/Pdt./1994. The research employs a juridical-normative approach within qualitative research, gathering data through literature review and interviews. The findings reveal that judges refer to existing legal provisions to determine compensation based on trial facts and the parties' circumstances. Secondly, the legal basis and considerations align with the principles of legal discovery and Islamic law, particularly the maqasid asy-syariah, such as hifz al-mal (protection of wealth) and hifz al-‘ird (protection of dignity and reputation). This study underscores the judge's role in upholding justice and the subjective rights of the parties in the context of Sharia Economics. AbstrakKeterbatasan regulasi dalam menetapkan ganti rugi akibat perbuatan melawan hukum mendorong hakim Pengadilan Agama untuk melakukan ijtihad hukum. Penelitian ini bertujuan untuk mengkaji penetapan ganti rugi dalam sengketa Ekonomi Syari’ah yang melibatkan perbuatan melawan hukum. Kasus konkret dalam penelitian ini adalah perkara nomor 84/Pdt.G/2019/PA.Yk, di mana penggugat menuntut ganti rugi karena tergugat menutup buku tabungan BTN Syari’ah tanpa konfirmasi. Majelis hakim memutuskan untuk mengabulkan tuntutan ganti rugi, merujuk pada Pasal 1375 dan 1372 KUHPerdata, serta yurisprudensi nomor 650/PK/Pdt./1994. Pendekatan yang digunakan adalah yuridis-normatif dalam penelitian kualitatif, dengan pengumpulan data melalui studi kepustakaan dan wawancara. Hasil penelitian menunjukkan bahwa, pertama, hakim mengacu pada ketentuan hukum yang ada untuk menetapkan ganti rugi, berdasarkan fakta-fakta di persidangan dan kondisi para pihak. Kedua, dasar hukum dan pertimbangan hakim sejalan dengan prinsip penemuan hukum dan hukum Islam, terutama maqasid asy-syariah, seperti hifz al-mal (perlindungan harta) dan hifz al-‘ird (perlindungan martabat dan nama baik). Penelitian ini menyoroti peran hakim dalam menjaga keadilan dan hak-hak subjektif para pihak dalam konteks Ekonomi Syari’ah.